MISI MULTIKULTURAL YESUS KEPADA PEREMPUAN KANAAN BERDASARKAN MATIUS 15:21-28 - Adi Putra; Yane Henderina Keluanan (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
This research is about Jesus' multicultural mission to Canaanite women based on Matthew 15:21-28. This study examines the nature and principles of the task carried out by Jesus to the Canaanite women. Interestingly, the church often considers Jesus' mission exclusively for the Jews. However, this case shows that the mission was opened to non-Jewish nations. By using qualitative research methods, this study obtained several conclusions. First, based on the description of the interpretation of Matthew 15:21-28 and taking into account the context and background of the Canaanite woman, it is clear that Jesus' ministry or mission to Canaanite women is clear is a multicultural mission. Second, Jesus' ministry to Canaanite women (Matt. 15:21-28) qualifies as a multicultural mission because it has fulfilled all theologies that are part of multicultural theology, such as relational, social, operational, moral, and transformational theology. Third, Jesus' ministry to the Canaanite woman (Matt. 15:21-28) fulfills every aspect of the Christocentric dimension in the construction of multicultural theology.